water vision making water everybody's business - Cosgrove, William J. | Rijsberman, Frank R. (Estados Unidos | ESTADOS UNIDOS Earthscan / Washington, 2000)
Contents: Vision statement and key messages; The use of water today; Water futures; Our vision of water and life in 2025; investing for the water future
Sin Especificar
Keywords: Agua